IMPLEMENTASI PROGRAM WAJIB TANAM BAWANG PUTIH LOKAL BAGI IMPORTIR DI JAWA TIMUR - Firliah, Nyahni Arisandi; Mubarokah, Mubarokah; Soedarto, Teguh (Agridevina : Berkala Ilmiah Agribisnis, 2021)
The purpose of this study was to study the development of garlic imports in East Java during the last ten years, the factors affecting the level of garlic imports in East Java, and the implementation of the mandatory garlic planting program in East Java through the perception of garlic importers. The research method was carried out by processing primary data using interview sessions, observational observations, literature study and documentation. Secondary data using statistical analysis test methods. The result of this research is the development of garlic production volume has increased seen from the level of production before and after the implementation of the compulsory garlic planting program by importers. However, the volume of imported garlic continues to increase in line with the amount of consumer demand. Consumption has a positive effect on garlic imports in East Java. The harvested area has a negative and insignificant effect on garlic imports in East Java. Import prices have a negative and insignificant effect on garlic imports in East Java. The population of East Java has a negative and insignificant effect on garlic imports in East Java. The rupiah exchange rate against the dollar has a negative and insignificant effect on garlic imports in East Java. The compulsory planting program is said to be successful based on differences in the amount of production before and after it was implemented. The amount of production which gradually increases compared to before the enactment of PERMENTAN N0. 38 of 2017 concerning Horticultural Product Import Recommendations. DOI : https://doi.org/10.33005/adv.v10i2.2913